High Density Lipoprotein Structure–Function and Role in Reverse Cholesterol Transport - Lund-Katz, Sissel (2010)
High density lipoprotein (HDL) possesses important anti-atherogenic properties and this review addresses the molecular mechanisms underlying these functions. The structures and cholesterol transport abilities of HDL particles are determined by the properties of their exchangeable apolipoprotein (apo) components. ApoA-I and apoE, which are the best characterized in structural terms, contain a series of amphipathic α-helical repeats. The helices located in the amino-terminal two-thirds of the molecule adopt a helix bundle structure while the carboxy-terminal segment forms a separately folded, relatively disorganized, domain. The latter domain initiates lipid binding and this interaction induces changes in conformation; the α-helix content increases and the amino-terminal helix bundle can open subsequently. These conformational changes alter the abilities of apoA-I and apoE to function as ligands for their receptors. The apoA-I and apoE molecules possess detergent-like properties and they can solubilize vesicular phospholipid to create discoidal HDL particles with hydrodynamic diameters of ~10 nm. In the case of apoA-I, such a particle is stabilized by two protein molecules arranged in an anti-parallel, double-belt, conformation around the edge of the disc. The abilities of apoA-I and apoE to solubilize phospholipid and stabilize HDL particles enable these proteins to be partners with ABCA1 in mediating efflux of cellular phospholipid and cholesterol, and the biogenesis of HDL particles. ApoA-I-containing nascent HDL particles play a critical role in cholesterol transport in the circulation whereas apoE-containing HDL particles mediate cholesterol transport in the brain. The mechanisms by which HDL particles are remodeled by lipases and lipid transfer proteins, and interact with SR-BI to deliver cholesterol to cells, are reviewed.